Aktivitas Antimikroba Ekstrak Jahe Kering Beku Terhadap Beberapa Bakteri Patogen - Siti Nurjanah; Sarah Fathia (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2017)
Ginger (Zingiber officinale Roscoe) has a potential as antimicrobial agent by inhibit or kill microbes. Freeze dried ginger extract is prepared for applying into food matrix easily. The objectives of this study was to evaluate the antimicrobial activity of freeze dried ginger extracts by multistage maceration using hexane, ethyl acetate and etanol against foodborne pathogen Staphylococcus aureus, Bacillus cereus and Salmonella enterica serovar Typhimurium. Ginger extracts were prepared by multistage maceration method using with different polarity of solvents i.e. hexane, ethyl acetate and etanol then freezed dried. Antimicrobial activity of the ginger extract were assayed by agar well diffusion method with Diameter Inhibition Zone (DIZ) and dillution broth method. The yield of hexane, ethyl acetate and etanol ginger extracts from multistage maceration were respectively 3.57; 3.17; 3.02 g/100 g dry ginger. The DIZ value of hexane, ethyl acetate and etanol ginger extracts for Staphylococcus aureus were 5.0, 5.7, 1.3 mm respectively and 6.1, 6.6, 6.0 mm for Bacillus cereus, however there was no inhibitory zone for Salmonella Typhimurium. The ethyl acetate ginger extract showed highest inhibition zone. The ethyl acetate ginger extract can reduced the growth of B.cereus and S. aureus as much as 85 and 47% from the normal growth level, however required higher concentration for reach 90% reduction.